Analysing The Causes And Challenges Of Recurrent Hernias: Insights From Surgical Practice - shakya, Jps; singh, Prakhar; Khandelwal, Shivam; kumar, Shiv (Journal of Neonatal Surgery, 2025)
Background: Recurrent hernias continue to present themselves as a problem in surgical practice and a burden to healthcare, worsening the quality of life of the patient. Even in cases of apparently satisfactorily conducted surgical repair, many factors of a technical, patient-related, and anatomical nature may contribute to recurrence. It is, therefore, necessary to understand these multiple causes to devise targeted preventive strategies and improve patient outcomes. Methods: A systematic analytical review of the data was obtained from databases including Medline, PubMed, Scopus, Embase, Springer Link, and Cochrane Library. This review emphasized articles on different hernia types (inguinal, incisional, umbilical, femoral) and their recurrence rates, modifiable risk factors, technical approaches, open and laparoscopic, and outcomes following surgery. The reference lists of these pertinent articles were also checked for additional relevant studies. Attention was paid to both technical and non-technical aspects that could be responsible for recurrence, including chemo-preventive measure and surgical advancements that reduce the chance of relapse. Results: The recurrent hernias are the result of inadequate operative technique, mesh-related complications, and patient-specific risks, including being overweight, smoking, and chronic intra-abdominal pressure. Lichtenstein tension-free mesh repair is the gold standard for inguinal hernias, whereas laparoscopic IPOM and open sublay techniques might be considered for incisional hernias. Despite such techniques, the recurrence rate for inguinal hernias ranges from 0.2% to 10% and can reach 25-32% for incisional hernias, 1-43% for umbilical hernias, and around 6% for femoral hernias. Advanced age, poor tissue quality, and noncompliance with postoperative care further complicate the risk of relapse. Conclusion: Addressing recurrent hernias requires a multifactorial approach that combines meticulous surgical technique with identification and modification of the patient-specific risk factors items and an assurance of robust follow-up. New clinical research and developments relating to the mesh materials, surgical modalities, and patient optimization may reduce the overwhelming burden of recurrent hernias. It will require the collaboration of surgeons, researchers, and policymakers to promulgate evidentiary-based guidelines and greatly improve patient outcomes